The effects of the administration sequence and the type of hypnotics on the development of remifentanil-induced chest wall rigidity: a randomized controlled trial - Yu Jin Oh; Yesull Kim; Chanhong Lee; Dong-Chan Kim; Aram Doo (BMC Anesthesiology, 2023)
Abstract Background Research on remifentanil-induced chest wall rigidity is limited. Furthermore, its incidence is unknown, and the clinical factors influencing its development remain unclear. This prospective, double-blind, randomized controlled trial aimed to investigate the effects of the administration sequence of hypnotics and remifentanil as well as the type of hypnotic administered on the development of remifentanil-induced chest wall rigidity. Methods A total of 125 older patients aged $$\ge$$ ≥ 65 years, who were scheduled to undergo elective surgery under general anesthesia, were enrolled in this study. Participants were randomly assigned to one of four groups; Thio-Remi, Pro-Remi, Remi-Thio, or Remi-Pro. After confirming the loss of consciousness and achieving a target effect-site concentration of 3 ng/mL remifentanil, the development of remifentanil-induced chest wall rigidity was evaluated. Results The incidence of chest wall rigidity was significantly higher in the remifentanil-hypnotic group than in the hypnotic-remifentanil (opposite sequence) group (55.0% vs. 21.7%, P < 0.001). Logistic regression analysis revealed that remifentanil-hypnotic administration was a significant predictor of the development of chest wall rigidity (crude odds ratio 4.42, 95% confidence interval 1.99; 9.81, P < 0.001). Conclusions Pretreatment with hypnotics potentially reduces the development of chest wall rigidity during the induction of balanced anesthesia with remifentanil in older patients. Trial registration This article was registered at WHO International Clinical Trials Registry Platform (Trial number: KCT0006542).